Loving Pablo hating Escobar - Vallejo, Virginia 1949-; Jusid, Federico 1973- (Universum Film GmbH, 2018)
"A journalist strikes up a romantic relationship with notorious drug lord Pablo Escobar." [imdb-com]
Special features: Interviews mit Penelope Cruz, Javier Bardem und Peter Sarsgaard ; Trailer
Bildformat 2.40:1 (16:9 anamorph)
Original: Spanien, Bulgarien 2017
Keywords: Film; DVD-Video